Compressing instruction time into fewer years of schooling and the impact on student performance - Mathias Huebener; Jan Marcus (Economics of Education Review, 2017)
Is it possible to compress instruction time into fewer school years without lowering education levels? A fundamental reform in Germany reduced the length of academic track schooling by one year, while increasing instruction hours in the remaining school years to provide students with a very similar core curriculum and the same overall instruction time. Using aggregated administrative data on the full population of students, we find that the reform increases grade repetition rates and lowers final grade point averages, without affecting graduation rates. The results suggest adverse reform effects on student performance, but the economic significance of the effects appears moderate.
Keywords: I21; I24; I28; J18; D04; 330; Instruction time; Student performance; G8 education reform; Difference-in-differences; Wild cluster bootstrap